Eisen Tamkun: capstone - Tamkun, Eisen, artist (Colorado State University. Libraries, 2019)
The artist's statement: Every day we experience thousands of interactions, both big and small. It is easy to get caught up in the speed of everyday life; to forget the who and the what which have shaped us into the persons we are today. There are moments which hold a great deal of meaning and those which hold very little, and yet all contribute to the being we become. Each one has gifted me with an understanding of myself and the world around me. I am also fortunate to have a family that has taught me a great deal. This body of work focuses on these relationships and experiences in my life, and the influences they have had on me as a person. In my piece Links, I focus on the overarching experiences and situations which shape us into the people we are. Each ring is unique. They are arranged in a way that loosely map my own meaningful experiences. This work is also intended to allow the viewer to find their own story within the chain. Through the process of examining different qualities and patterns of the links, they may contemplate their own life experiences and reflect on the moments that have significant, either great or small. Siblings, is a series of work representing the relationship with my three siblings, as well as myself. Each piece uses topographical lines drawn from our birthplaces. The brooch format provides a platform from which each relationship can be displayed. When worn, the front is facing out, a projection into the public space. The back, however, rests against the wearers body, close to the chest, hidden from sight. The color seen on the front of each piece represents the perception each sibling has of themselves. The colors found on the back side are interpretations of the emotions I feel when thinking about the relationship we share with each other. The piece Disperse, is specific to my challenges of being a twin. Forming an individual identity alongside my twin was an ongoing struggle throughout childhood. Each fetal form can be detached from the piece and be worn as a brooch. This separation, not only from the body of the piece, but from each other, emphasizes the severance of children from the safety of home. The realization that we have our own obstacles to overcome and our distinct talents to help us do so, aids in the construction of our own separate identities. The exploration and creation of these pieces gives me a greater appreciation for the interactions which shape our lives.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: metalsmithing and jewelry